Small business entrepreneur resistance of ICT adoption: a lesson from Indonesia. (2018) - Suhartanto, Dwi; Leo, Gundur
The availability of information and communication technology (ICT) has assisted business organisations to effectively produce and market their products and services in the global market. However, many small businesses have not adopted such technology, especially online stores and websites, to support their business activities. This paper examines small business entrepreneur resistances to adopting online store and website technology. This qualitative study uses the technology adoption model (TAM) as a theoretical basis. Using a sample of 131 small Indonesian business entrepreneurs, this study reveals that perceived lack of usefulness, perceived lack of ease to use, resources, and social influences are resistance factors for entrepreneurs to adopt online stores and websites. Further, among these factors, the perceived lack of usefulness and resources is considered the most substantial resistance factor for the entrepreneur to adopt the technology. This study extends our understanding that TAM is also a useful theory to explain the resistance of adopting the technology. The managerial impact and possible future research is also discussed.